Designing a Model of Fear of Missing Out (FoMO) Based on Parenting Styles with the Mediating Role of Brain Behavioral Systems in Female University Students Using Virtual Space - Taghvaei, Pegah; Mohagheghi, Hossein; Yaghoobi, Abolghasem; Yarmohammadi Vasel, Shahriar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The aim of this study was to design a model of Fear of Missing Out (FoMO) based on parenting styles with the mediating role of brain behavioral systems among female university students who are users of virtual space. Methods and Materials: The research method was descriptive–correlational and was conducted within the framework of structural equation modeling (SEM). The statistical population consisted of undergraduate female students at the Islamic Azad University, Arak branch, from which 224 participants were selected using convenience sampling. Data were collected using the Baumrind Parenting Styles Questionnaire, the Behavioral Inhibition System and Behavioral Activation System Scales, and the FoMO Scale. Data analysis was performed using SPSS version 27 and AMOS version 24. Findings: Model fit indices indicated an acceptable fit to the data (χ²/df > 3, RMSEA = 0.08, AGFI < 0.90, CFI < 0.90). Direct path coefficients showed that the authoritative parenting style had significant relationships with behavioral inhibition, behavioral activation, and FoMO (p ≤ 0.01). Direct effects between the authoritarian parenting style and behavioral inhibition, behavioral activation, and FoMO were also significant (p ≤ 0.01). Additionally, direct relationships between the permissive parenting style and both behavioral inhibition and behavioral activation were significant (p ≤ 0.01), but its relationship with FoMO was not significant (p ≥ 0.05). Indirect effects were significant in all cases. Conclusion: The findings indicate a significant mediating role of brain behavioral systems in the relationship between parenting styles and FoMO. Overall, the results highlight the importance of parenting styles and brain behavioral systems in explaining the phenomenon of FoMO.